2012
DOI: 10.1177/0954407012440075
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of gasoline and diesel mixtures on partially premixed combustion and comparison with the practical fuels gasoline and diesel in a compression ignition engine

Abstract: If fuels that are more resistant to autoignition are injected near top dead centre in compression ignition engines, they ignite much later than diesel fuel does, and combustion occurs when the fuel and air have had more chance to mix. This helps to reduce nitrogen oxide and smoke emissions. Moreover, this can be achieved at much lower injection pressures than for a diesel fuel. However, it is preferable to have fuels with a lower research octane number than those of commonly available gasolines, because this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…9(c) shows the un-burnt hydrocarbon amount versus (G/D) ratio; it shows that when increasing gasoline ratio in the mixture, the un-burnt hydrocarbon fraction formed near the cylinder wall increases which results in an incomplete combustion. The same results have been confirmed by Micklow et al [5] and Yang et al [22]. Additionally, the proposed model confirms that n-heptane, the most-reactive fuel component, burns at a faster rate compared to iso-octane which is less-reactive [15].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…9(c) shows the un-burnt hydrocarbon amount versus (G/D) ratio; it shows that when increasing gasoline ratio in the mixture, the un-burnt hydrocarbon fraction formed near the cylinder wall increases which results in an incomplete combustion. The same results have been confirmed by Micklow et al [5] and Yang et al [22]. Additionally, the proposed model confirms that n-heptane, the most-reactive fuel component, burns at a faster rate compared to iso-octane which is less-reactive [15].…”
Section: Resultssupporting
confidence: 81%
“…However, the effects of gasoline blending on combustion performance and exhaust emissions diminished as the engine load increased. Yang et al [22] investigated different dual-fuel combustion modes (gasoline /diesel blend) on diesel engine performance and emissions. Highly Premixed Charge Combustion (HPCC) and (LTC) modes have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that GCI requires appropriate stratification to ensure combustion at low loads and to mitigate high heat release rates at high loads, it might indeed be better to have larger hole sizes. In fact, preliminary experiments by Won et al 53,54 demonstrated, in a single-cylinder engine, that the operating limits can be extended by larger-diameter injector nozzle holes and lower injection pressures. Since mixture preparation is so critical in GCI engines, other injector parameters such as the included angle 36 have to be optimized with the combustion bowl shape.…”
Section: Gasoline Compression Ignition (Gci): Principles and Mechanismsmentioning
confidence: 99%
“…One alternative might be to use mixtures of gasoline and diesel, ''dieseline'', to reduce the octane number of the market gasoline to better enable GCI technology e.g. [8,9]. Blends with gasoline concentrations of 50% by volume or more (most likely between 80% and 90% by volume gasoline) would be of interest for such applications.…”
Section: Introductionmentioning
confidence: 98%